THE INFLUENCE OF MOTHER'S EDUCATION LEVEL ON STUNTING IN CHILDREN - Veny Eka Yogawati (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
Stunting is a condition where there is a delay or even failure of growth and development in toddlers (infants under 5 years old), which results in chronic malnutrition so that the child is too short for his age. Malnutrition is a cause of infant mortality in Indonesia. Malnutrition occurs from the baby in the womb and in the early stages of the baby's birth. The mother's education level is one factor in meeting the nutritional needs of the family, especially in children. The purpose of this study was to identify the influence of maternal education level on stunting in children. This research method uses a case study design. The subjects of this study were mothers who have children under 5 years old in Besuk Agung Village, Besuk District, Probolinggo Regency. A study was conducted on 166 mothers who have children under 5 years old. Maternal education level was determined by the formal education that has been completed, stunting was determined by the z-score indicator for body length according to age. The results of this study found a significant influence between maternal education and the incidence of stunting in children under 5 years old in Besuk Agung Village. Mothers with low education levels are at greater risk of having stunted children. Maternal education plays a crucial role in stunting among children under 5 years of age in Besuk Agung village. Education is a practical way for mothers to more easily absorb health information.